Multi-analyte high performance liquid chromatography coupled to high resolution tandem mass spectrometry method for control of pesticide residues, mycotoxins, and pyrrolizidine alkaloids - Dzuman, Zbynek; Zachariasova, Milena; Veprikova, Zdenka; Godula, Michal; Hajslova, Jana (Analytica chimica acta, 2015)
A new reliable and highly sensitive method based on high performance liquid chromatographic (HPLC) separation and high resolution tandem mass spectrometric detection (HRMS/MS) has been developed and validated for determination of 323 pesticide residues, 55 mycotoxins, and 11 plant toxins represented by pyrrolizidine alkaloids. The method was validated for three matrices, leek, wheat, and tea differing in nature/amount of co-extracts that may cause various matrix effects. For target analytes isolation, optimized QuEChERS-based (quick, easy, cheap, effective, rugged, and safe) extraction procedure was employed. Spectral HRMS/MS library has been established providing an entire spectrum of fragment ions for each analyte, which allows unbiased identification and confirmation of target compounds. The limits of quantification (LOQs) of target analytes were below 10 μg kg(-1) for 82%, 81%, and 61% for matrices leek, wheat, and tea, respectively. Recoveries were in the acceptable range (70-120%) according to SANCO/12571/2013 for most of target analytes, except for highly polar 'masked' mycotoxin deoxynivalenol-3-glucoside with recoveries 35%, 47%, and 42% for matrices leek, wheat, and tea, respectively. The linearities of calibration curves expressed as coefficients of determination were in the range of 0.9661-1.000, and repeatabilities expressed as relative standard deviations (RSDs) at LOQs lied in the range of 0.25-13.51%. The trueness of the method was verified using several certified reference materials (CRMs) and proficiency test samples.
Keywords: Mycotoxins; vysokoúčinná kapalinová chromatografie; Molecular Structure; Pyrrolizidine Alkaloids; molekulární struktura; pyrrolizidinové alkaloidy; Chromatography, High Pressure Liquid; Pesticide Residues; High resolution tandem mass spectrometry; tandemová hmotnostní spektrometrie; Pesticide residues; Quick easy cheap effective rugged safe; rezidua pesticidů; Orbitrap; High performance liquid chromatography; mykotoxiny; Tandem Mass Spectrometry